The Pentagon's battle for the American mind : the early Cold War - Bogle, Lori Lyn (Texas A & M University military history series, 2004)
"The U.S. military has historically believed itself to be the institution best suited to develop the character, spiritual values, and patriotism of American youth. In The Pentagon's Battle for the American Mind, Lori Lyn Bogle investigates how the armed forces assigned themselves the role of guardian and interpreter of national values and why they sought to create "ideologically sound Americans capable of defeating communism and assuring the victory of democracy at home and abroad.""--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved